2022
DOI: 10.2478/sjph-2022-0028
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index as a proxy indicator for poor oral hygiene habits in adult diabetic patients

Abstract: Aim To analyse if body mass index (BMI) could be used as a fast proxy indicator of poor oral hygiene habits (POHH) among the adult population with diabetes mellitus. Methods Adults, aged 25-74, from the Slovenian 2016 nationwide cross-sectional survey based on the Countrywide Integrated Non-Communicable Disease Intervention (CINDI) Health Monitor methodology, who reported being diabetic, were included in the study (n=560). We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
0
0
Order By: Relevance
“…This distribution may influence our findings, especially considering previous studies suggesting a reciprocal relationship between fewer teeth and obesity (21,35). It has also been reported that BMI can be a valuable tool for predicting poor oral hygiene habits in diabetic patients, and thereby possible oral health issues in this population (36).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This distribution may influence our findings, especially considering previous studies suggesting a reciprocal relationship between fewer teeth and obesity (21,35). It has also been reported that BMI can be a valuable tool for predicting poor oral hygiene habits in diabetic patients, and thereby possible oral health issues in this population (36).…”
Section: Discussionmentioning
confidence: 81%
“…It has also been reported that BMI can be a valuable tool for predicting poor oral hygiene habits in diabetic patients, and thereby possible oral health issues in this population ( 36 ).…”
Section: Discussionmentioning
confidence: 99%